2002
DOI: 10.1590/s0066-782x2002001300001
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of different indices of cardiac risk for patients undergoing noncardiac surgeries

Abstract: The cardiac risk indices currently used did not show a better accuracy than that obtained randomly. None of the indices proved to be significantly better than the others. Studies to improve our ability to predict such complications are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…In the preoperative evaluation, each factor is added; the higher the sum, the greater the risk of death due to a cardiac reason and of life-threatening cardiac events, such as myocardial infarction, pulmonary edema, and ventricular tachycardia. 10 …”
Section: Introductionmentioning
confidence: 99%
“…In the preoperative evaluation, each factor is added; the higher the sum, the greater the risk of death due to a cardiac reason and of life-threatening cardiac events, such as myocardial infarction, pulmonary edema, and ventricular tachycardia. 10 …”
Section: Introductionmentioning
confidence: 99%
“…It concluded that none of the indexes analyzed were significantly superior to the others and that they did not show better accuracy than that which would be obtained by chance, according to the results found: areas under the ROC curve 0.48 (± 0.03) for the Goldman, ASA and Larsen scale and 0.38 (± 0.03) for the Detsky scale. 11 Another prospective study compared the EMAPO to the ACP method to determine heart risk in non-cardiac surgeries and to find new variables involved in determining this risk. The results revealed that there was no difference between the two methods, and that the EMAPO was as effective as the American College of Physicians for determining the risk of cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…These algorithms are not perfect 28 , but all of them are better than chance in predicting perioperative complications and should be used during the evaluation. All of them have advantages and disadvantages that should be considered during their use.…”
Section: Considerations On the Preoperative Cardiac Evaluation Algorimentioning
confidence: 99%